Is the eldest son different? The residential choice of siblings in Japan - Midori Wakabayashi; Charles Yuji Horioka (Osaka University, Institute of Social and Economic Research (ISER), 2006)
In this paper, we analyze the determinants of the living arrangements of elderly parents and their children (whether elderly parents live with their children, and if so, with which child) in Japan using micro data from a household survey. We find that the proportion of elderly parents living with their eldest sons is much higher than that of elderly parents living with children other than the eldest son, even if the eldest son is not the eldest child. Moreover, we find that elderly parents are more likely to live with their eldest sons if the father was a self-employed worker before retirement, whereas they are more likely to live with a child other than the eldest son if the father was an executive before retirement. In addition, daughters whose husbands adopt the daughter's surname are more likely to live with the daughter's parents. All of these findings are consistent with the dynasty and/or strategic bequest (selfish life cycle) models. We also find that the living arrangements of elderly parents are still very much based on Japanese social norms and traditions. Thus, we find support for all models of household behavior other than the altruism model.
Keywords: D12; D91; J14; Z13; 330; Aged; Altruism Model; Bequest Motive; Bequests; Care of the Elderly; Children; Consumer Economics; Co-residence; Culture; Dynasty Model; Economics of the Elderly; Elderly; Eldest Son; Family Business; Family Economics; Family Line; Household Behavior; Japan; Life Cycle Model; Living Arrangements; Parents; Primogeniture; Residential Choice; Siblings; Social Norms; Strategic Bequest Model; Strategic Bequest Motive; Traditions; Familiensoziologie; Eltern; Kinder; Lebensgemeinschaft; Japan